What Helped Support Nurses in the ED at CWM during the COVID-19 Outbreak in Fiji in 2021?. (November 2022) - Douglas, Bronte; Sosefo, Mamatuki; Keshni, Singh; Brown, Di; Robinson, Antony
Abstract : Background/Introduction: Following a quarantine breach in April 2021, Fiji went from no cases of COVID-19 to having the highest number per capita in the world. Fiji was relatively well-prepared to respond to COVID-19 as it has strong emergency management response systems. Nevertheless, due to the rapid increase, the public health system was quickly overwhelmed. The problem was particularly acute at the main tertiary hospital in Suva. Objectives: To describe the effects of an overwhelming COVID-19 outbreak on nurses working in the Emergency Department of Colonial War Memorial Hospital in Fiji, in 2021. To describe the lessons learned and recommendations for the future. Method/Description: Focus Group Discussion with two groups of nurses: (1) ED nurse and (2) nurses seconded to provide a surge workforce in the most acute phase. Results/Outcomes: Preliminary findings show that nurses were lacking in confidence and frightened about the growing epidemic. Resources, material and human, were initially in short supply. The agency of the nurses as result of their post-graduate study and due to the collegial environment in ED resulted in increased supplies of PPE and changes to nursing practice (eg, web-based handover). Final results pending. Conclusion: The preliminary findings of this research illustrate that even in low-resource settings, with the right support and effective nursing leadership, nurses can provide safe and effective care to patients. The research illustrates the benefits of sound, relevant education, the crucial importance of teamwork, the importance of networks, the important benefits of early deployment of the MET, and the need for effective nursing leadership.